Formation and Accumulation of Pore Methane Hydrates in Permafrost: Experimental Modeling - Evgeny Chuvilin; Dinara Davletshina (Geosciences, 2018)
Favorable thermobaric conditions of hydrate formation and the significant accumulation of methane, ice, and actual data on the presence of gas hydrates in permafrost suggest the possibility of their formation in the pore space of frozen soils at negative temperatures. In addition, today there are several geological models that involve the formation of gas hydrate accumulations in permafrost. To confirm the literature data, the formation of gas hydrates in permafrost saturated with methane has been studied experimentally using natural artificially frozen in the laboratory sand and silt samples, on a specially designed system at temperatures from 0 to −8 °C. The experimental results confirm that pore methane hydrates can form in gas-bearing frozen soils. The kinetics of gas hydrate accumulation in frozen soils was investigated in terms of dependence on the temperature, excess pressure, initial ice content, salinity, and type of soil. The process of hydrate formation in soil samples in time with falling temperature from +2 °C to −8 °C slows down. The fraction of pore ice converted to hydrate increased as the gas pressure exceeded the equilibrium. The optimal ice saturation values (45−65%) at which hydrate accumulation in the porous media is highest were found. The hydrate accumulation is slower in finer-grained sediments and saline soils. The several geological models are presented to substantiate the processes of natural hydrate formation in permafrost at negative temperatures.